A novel Raman spectroscopic approach to identify polymorphism in leflunomide: a combined experimental and theoretical study. (2nd December 2015) - Sharma, Poornima; Gangopadhyay, Debraj; Umrao, Sima; Kumar, Shiv; Ghosh, A. K.; Mishra, P. C.; Singh, Ranjan K.
Abstract : Polymorphism is an important characteristic which affects the activity, solubility and other physical properties of a compound and can be induced by varying temperature, pressure and solvent. The presence and conversion of α to β polymorphic forms of an anti‐rheumatic drug leflunomide have been studied by temperature‐dependent and in situ Raman observations. Both α and β polymorphs were found to co‐exist in the temperature interval 367–372 K. The α form alone exists below 367 K and the β form alone above 373 K. The CO stretching band clearly demonstrates the α → β conversion because of breaking of N–H···O bond and formation of N–H···N bond. On cooling the Raman spectra suggest the irreversibility of this conversion. Thermodynamic stability, crystal parameters and surface morphology of both forms in the leflunomide powder used for the present study have been verified by differential scanning calorimetry, X‐ray powder diffraction and scanning electron microscopy. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A novel Raman spectroscopic approach has been applied to identify polymorphism in leflunomide. Temperature‐dependent Raman spectra clearly depict the presence of α and β polymorphs of leflunomide and also their coexistence at different temperature ranges. The conversion of α form to β form is observed precisely using in situ Raman measurement between 372 and 373 K. The Raman results are supported by theoretical density functional theory calculations along with other experimental techniques, viz. differential scanning calorimetry, X‐ray powder diffraction and scanning electron microscopy.